Synbiotic encapsulation against Vibrio parahaemolyticus infection in whiteleg shrimps - Wei, Guangmin (2024)
Vibrio parahaemolyticus is a severe pathogenic bacterium which causes significant mortality and economical loss in shrimp farming. To control vibriosis in whiteleg shrimps (Litopenaeus vannamei), we developed synbiotic beads by microencapsulating probiotic of Lactobacillus plantarum and prebiotic of xanthan gum in agarose matrix through emulsion technique. Coculture method indicated that synbiotic beads reduce viability of Vibrio parahaemolyticus by 3 orders of magnitude. The high inhibitory activity of synbiotic beads against pathogen could result from the antibacterial substances secreted from encapsulated probiotics, and access blocking of pathogens to prebiotics as food source so that the encapsulated prebiotics solely stimulate nearby probiotic growth without boosting pathogen growth. Bacterial challenge test indicated that exposure to synbiotic beads in advance can delay mortality and increase shrimp survival from 10% to 57%. As a smart encapsulation platform, our design can be extended to various probiotics, prebiotics, and pathogens, thus providing an alternative strategy to the use of antibiotics for disease prevention and sustainable aquaculture.